Antioxidant activity and modified release profiles of morin and hesperetin flavonoids loaded in Mg- or Ag-modified SBA-16 carriers. (September 2020) - Trendafilova, Ivalina; Mihály, Judith; Momekova, Denitsa; Chimshirova, Ralitsa; Lazarova, Hristina; Momekov, Georgi; Popova, Margarita
Graphical abstract: Abstract: The problems related with low solubility and instability in physiological environment of flavonoids are currently a challenge for their potential application for prevention and therapy of major chronic diseases, including cardiovascular and neurodegenerative diseases, cancer etc. Promising approach to overcome these drawbacks is incorporation of these compounds into mesoporous silica carriers. In this study we develop SBA-16 silica nanoparticles modified by a post-synthesis method with Mg (4 wt.%) or Ag (4 wt.%) as a carriers for simultaneous delivery of poorly soluble biological active compounds and essential micronutrients or antimicrobial agents. Hesperetin, a natural flavonone, and morin, a natural flavonol, belong to the big family of flavonoids were loaded by incipient wetness impregnation on the parent and Ag- or Mg-modified mesoporous supports. The initial, modified and drug loaded SBA-16 materials were characterized by powder XRD, N2 physisorption, thermogravimetric analysis and SEM measurements. The interactions between metals, silica surface and flavonoids were studied by ATR-FTIR and UV–Vis spectroscopies. Improved release profiles are observed for flavonoids loaded in mesoporous materials in comparison with pure flavonoids. Loading of flavonoids in parent and modified mesoporous carriers made the sustained delivery of the bioactive compound possible. A comparative study on anti-proliferative effect of the tested flavonoids loaded into modified silica carriers vs. free drug was investigated on a panel of three human cell lines. The evaluation of the antioxidant capacity shows that loading of the flavonoids into parent and modified silica supports can improve their activity against free radicals, which could be explained by the improved solubility of the loaded flavonoids in comparison with the pure ones. The obtained mesoporous delivery systems are promising as oral formulations for delivery of flavonoids, essential microelements and antimicrobial agents.